PENGARUH ATRIBUT PRODUK TERHADAP MINAT BELI ULANG KOSMETIK MERK MAYBELLINE PADA KONSUMEN DI KOTA BANJARMASIN - - Mailiana; Ni Nyoman Suarniki (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Abstract, The purpose of this research was to determine the effect of product attributes (brand, quality, design, packaging, label, and service) on the repurchase interest of Maybelline cosmetics among consumers in the city of Banjarmasin both partially, simultaneously, and most dominantly. The population in this research were 300 customers who used Maybeline's products, while the sample that was obtained was as many as 60 people. The method of data analysis in this study used multiple linear regression methods with the help of the SPSS version 22.0 application. The results of the research found that Maybelline's product attributes (brand, quality, design, packaging, label, and service) were good enough, using SPSS version 22.0 for windows. Of the six elements have a significant value on the repurchase interest of Maybelline cosmetics to consumers in the city of Banjarmasin. This research shows that the variables Brand (X1), Quality (X2), Design (X3), Packaging (X4), Label (X5), Service (X6) have a positive effect partially and simultaneously on repurchase interest. From the results of the coefficient of determination, the beta value of the largest number is 0.245 with the largest contribution of 21.5%, that the Design variable (X3) has a dominant influence on the repurchase interest of Maybelline cosmetics among consumers in the city of Banjarmasin.